PENGARUH INVESTASI ASING LANGSUNG DAN MODAL MANUSIA PADA PERTUMBUHAN EKONOMI INDONESIA: Endang Syahriani - syahriani, endang (indOmera, 2020)
This paper examines the role Foreign Direct Investment and Human Capital on Economic Growth in Indonesia. The data used in this research are time series data period from 1990 to 2012. Data obtained from the website of World Bank. The results showed that the Foreign Direct Investment and Human Capital affect economic growth in Indonesia. Of both independent variables, Human Capital variable compared to Foreign Direct Investment variable more affect economic growth.